2007
DOI: 10.1037/1524-9220.8.3.161
|View full text |Cite
|
Sign up to set email alerts
|

What about men? Social comparison and the effects of media images on body and self-esteem.

Abstract: Research has consistently shown that exposure to ideal female images negatively influences women's self-evaluations (e.g., Brown, Novick, Lord, & Richards, 1992;Henderson-King, Henderson-King, & Hoffman, 2001). However, minimal research has examined the effects of media-portrayed male images on men's self-evaluations. This article presents an exploratory investigation into the impact of media on men's views of themselves and their bodies. It was hypothesized that compared to men who viewed neutral images, men … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 64 publications
1
64
0
1
Order By: Relevance
“…In particular, the media are held responsible for the transmission of messages about the ideal body, which for boys and men is a lean but highly muscular, V-shaped figure, often referred to as the 'muscular mesomorph' (Mishkind, Rodin, Silberstein, & StriegelMoore, 1986). Although most of the existing research has investigated women, a few studies have suggested that exposure to idealized muscular media images is similarly related to lower body esteem (Hobza & Rochlen, 2009;Hobza, Walker, Yakushko, & Peugh, 2007), increased muscle dissatisfaction (Agliata & Tantleff-Dunn, 2004;Hargreaves & Tiggemann, 2009) and drive for muscularity in adult men (Cramblitt & Pritchard, 2013). However, two studies with adolescent boys found no relationship between body image or eating disorder symptomatology and magazine exposure (Jones, Vigfusdottir, & Lee, 2004) or thin-ideal media exposure (selected television programs and magazines) (Harrison, 2000).…”
Section: Introductionmentioning
confidence: 93%
“…In particular, the media are held responsible for the transmission of messages about the ideal body, which for boys and men is a lean but highly muscular, V-shaped figure, often referred to as the 'muscular mesomorph' (Mishkind, Rodin, Silberstein, & StriegelMoore, 1986). Although most of the existing research has investigated women, a few studies have suggested that exposure to idealized muscular media images is similarly related to lower body esteem (Hobza & Rochlen, 2009;Hobza, Walker, Yakushko, & Peugh, 2007), increased muscle dissatisfaction (Agliata & Tantleff-Dunn, 2004;Hargreaves & Tiggemann, 2009) and drive for muscularity in adult men (Cramblitt & Pritchard, 2013). However, two studies with adolescent boys found no relationship between body image or eating disorder symptomatology and magazine exposure (Jones, Vigfusdottir, & Lee, 2004) or thin-ideal media exposure (selected television programs and magazines) (Harrison, 2000).…”
Section: Introductionmentioning
confidence: 93%
“…According to this theory, people who perceive themselves as falling short of these expectations then experience distress (Hargreaves & Tiggemann, 2009;Harrison, 2001;Martin & Govender, 2011). The research on men's body image suggests that men's body satisfaction is, in fact, influenced by the internalized body ideals that men use when comparing their appearance with others and that falling short in the comparison may lead to body-related distress (Cahill & Mussap, 2007;Hobza, Walker, Yakushko, & Peugh, 2007;Jones, 2004;Karazsia & Crowther, 2008, 2010L. M. Schaefer & Thompson, 2014).…”
Section: Musculoskeletal Healthmentioning
confidence: 99%
“…Expecting to find that exposure to ideal-muscular body images on television would lead to an increase in body dissatisfaction, the researchers did indeed find that the men's dissatisfaction with their muscle size and physical attractiveness had increased while watching the muscular ideal commercials more than the control group (Hargreaves, Tiggermann 2009). Interestingly, though men's body-esteem is affected by exposure to muscular body types, their self-esteem was not affected (Hobza, Walker, Yakushko, Peugh 2007). However, certain studies says that when men are exposed to ideal image advertisements they become depressed, indicating that more research in the area is needed to reach a consensus on the subject (Agliata, Tantleff-Dunn, 2004).…”
Section: Gender Differencesmentioning
confidence: 99%
“…However, research has been increasingly focusing on males' body dissatisfaction (Morry, Staska 2001;Agliata, Tantleff-Dunn, 2004;Hobza, Walker, Yakushko, Peugh 2007). Though studies have discovered that both males and females do experience discontent with their body image, they have also given light to the differences in how males and females evaluate their physical appearance.…”
Section: Body Imagementioning
confidence: 99%
See 1 more Smart Citation